Krüppel-Like Factor 5 Mediates Cellular Transformation during Oncogenic KRAS-Induced Intestinal Tumorigenesis - Nandan, Mandayam O. (2007)
BACKGROUND & AIMS: Krüppel-like factor 5 (KLF5) is a zinc finger-containing transcription factor that regulates cell proliferation. Oncogenic KRAS mutations are commonly found in colorectal cancers. We aimed to determine whether KLF5 mediates KRAS functions during intestinal tumorigenesis. METHODS: The effects of KLF5 on proliferation and transformation were examined in IEC-6 intestinal epithelial cells stably transfected with an inducible KRAS(V12G). KLF5 expression was examined in intestinal tumors derived from transgenic mice expressing KRAS(V12G) under a villin promoter and in human colorectal cancers with mutated KRAS. RESULTS: Induction of KRAS(V12G) in IEC-6 cells resulted in increased expression of KLF5, accompanied by an increased rate of proliferation and anchorage-independent growth. Inhibition of KLF5 expression by MEK inhibitors or KLF5-specific small interfering RNA (siRNA) reduced proliferation and anchorage-independent growth despite KRAS(V12G) induction. Human colorectal cancer cell lines with mutated KRAS contained high levels of KLF5 and reduction of KLF5 by MEK inhibitors or KLF5 siRNA also led to reduced proliferation and transformation. In vivo, both intestinal tumors derived from mice transgenic for villin-KRAS(V12G) and human primary colorectal cancers with mutated KRAS contained high levels of KLF5 and increased staining of the proliferative marker, Ki67. CONCLUSIONS: Elevated levels of KLF5 protein are strongly correlated with activating KRAS mutations in intestinal tumors both in vitro and in vivo. Inhibition of KLF5 expression in these tumor cells resulted in significantly reduced rates of proliferation and transforming activities. We conclude that KLF5 is an important mediator of oncogenic KRAS transforming functions during intestinal tumorigenesis.